CUSTOMER SATISFACTION AND FINANCIAL PERFORMANCE: DOES IT MEDIATE CUSTOMER-CENTRIC ON ISLAMIC BANK VALUES? - Ulfi Kartika Oktaviana; Ahmad Tibrizi Soni Wicaksono (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to determine the influence of Customer-centric Corporate Social Responsibility (CSR) within the scope of Islamic Ethics on Company Values. In addition, this study also examines the role of customer satisfaction mediation and financial performance towards Customer-centric CSR with company values and tests the role of customer satisfaction mediation for Customer-centric CSR with financial performance. The sample used is Islamic Commercial Banks registered with BI with specified sample criteria. The data was processed using smartPLS, where the direct influence of Centric Customers in Islamic Ethics (CSR) on company values was significant. The Centric Customer variables in Islamic Ethics (CSR) influence financial performance. The other four hypotheses showed insignificant results. The results of the indirect influence test show that the variables of customer satisfaction and financial performance have not been able to mediate the relationship between Customer-centric in Islamic ethics and Company Values.